MOTHERS IN QUARANTINE: MOTHERHOOD IN TIMES OF SOCIAL ISOLATION DUE TO COVID-19 PANDEMIC - Okamoto, Mary Yoko [UNESP]; dos Santos, Manoel Antônio; Emidio, Thassia Souza (Universidade Estadual de Maringa, 2024)
This study aimed to analyze the impacts of the social isolation resulting from the COVID-19 pandemic on family life, with emphasis on the experience of motherhood and the relationship with children. Twenty mothers from the middle social strata, from 29 to 45 years old, who kept working activities at a distance and were in social isolation, participated. In-depth individual interviews were conducted by digital means. The collected material was transcribed and submitted to thematic content analysis. The results showed that the changes imposed by the pandemic directly impacted family life, highlighting gender inequalities in routine organization, distribution of household tasks and parental care. An ambivalent relationship was observed between mothers and maternity and their social imperatives, which reverberated in the bond they establish with their children. The analysis reveals that emotional and physical burden contributes to exacerbate feelings of guilt and loneliness experienced in the relationship with motherhood, in addition to showing conflicts in the performance of the roles of mother, wife and professional. The women interviewed showed exhaustion with domestic and child care demands, in addition to conflicts related to the mismatch between expectations and social standards that regulate the exercise of motherhood and their personal experiences as mothers. The conclusions suggest the presence of an identity crisis due to the social ideals linked to the experiences of motherhood, which invites us to think about the urgency of looking at maternal suffering, seeking to understand the subjective dimensions of the transformations that this experience goes through in the times of social isolation.
MADRES EN CUARENTENA: LA MATERNIDAD EN TIEMPOS DE AISLAMIENTO SOCIAL Y COVID-19
MÃES EM QUARENTENA: MATERNIDADE EM TEMPOS DE ISOLAMENTO SOCIAL DECORRENTE DA COVID-19
Keywords: Covid-19; Motherhood; psychoanalysis